Exploring Big Data Technology in Human Resources Decision-Making - Wang, Lizhi; Li, Xi; Zhang, Yulun (Transactions on Social Science, Education and Humanities Research, 2024)
With the widespread application of big data technology, human resources decision-making faces new opportunities and challenges. This paper explores the application of big data technology in human resources management and its potential impact, providing an in-depth analysis of the transformation of the role of HR managers in the era of big data. Firstly, the application of big data enables HR professionals to make more effective strategic business decisions by eliminating biases in decision-making and providing profound real-time insights. This, in turn, attracts and retains talented individuals, enhancing business efficiency. Secondly, big data plays a crucial role in the recruitment process, assisting management in avoiding recruitment errors. Personalized data analysis helps identify talents that match specific job requirements, ultimately improving long-term performance. Furthermore, the application of big data technology facilitates organized internal mobility of human resources within a unit. By analyzing employee data, organizations can gain better insights into employees' work capabilities and development potential, offering diverse opportunities for career development to enhance employee satisfaction, loyalty, and maintain competitiveness.